The Development of Tourism Areas in Abang Temple Yogyakarta, Using Engineering Geological Capability - Kristanto, Wisnu Aji Dwi; Utami, Ayu (Indonesian Journal on Geoscience, 2024)
Temples are interesting objects used for the exploration, exploitation, and development of tourist areas. However, these cultural sites and the surrounding environment need to be adequately preserved to prevent disasters. One of the interesting aspects of temples needed to be developed as tourist areas is its engineering geological capability. Therefore, this study aims to determine the engineering geological capability of Abang Temple located in the village of Jogotirto, Berbah, Sleman, Yogyakarta, Indonesia. This Buddhist heritage temple was built on an isolated hill with the constituent materials of red bricks, tuff, and andesite that have experienced weathering over the decades. The temple is geographically located in an interesting natural nuance, thereby making it a dilemma for developing tourist areas. This research was carried out by mapping and measuring field data on several influential aspects, including the carrying capacity of rocks and soil, slope, the potential for geological disasters, the depth of groundwater level, the ease of excavation, the land use, the rock weathering level, and the discontinuity field density. The results shows that there are three zones of engineering geological capability for developing temples into tourist areas, namely high, medium, and low capabilities.